Policy and practice in tenant participation: empowering tenants? - Redmond, Declan (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
This article presents the initial results of research into tenant participation across a number of different urban local authorities. Following this introduction, which sets out the context and background. the second section examines the theory and principles of tenant participation. The third section examines the implementation of tenant participation through a preliminary analysis of case studies from a number of urban local authorities across Ireland. The article concludes with some provisional conclusions regarding progress and limitations in the implementation of tenant participation.
Keywords: Urban geography -- Ireland